Exceptionalism or Chinamerica: Measuring Religious Change in the Globalizing World Today - Yang, Fenggang (Journal for the scientific study of religion, 2016)
Religion is changing fast in this era of globalization. Major global trends include the growth of Muslims, the shrinking percentage of unaffiliated, and the rapid rise of Christianity in global China. By 2030, China is likely to become the largest Christian country in the world while retaining large numbers of Buddhists, Muslims, and folk religious believers. To capture religious changes more accurately, social scientists of religion must sharpen their measurement tools regarding religiosity; pay more attention to the reality of nonalignment among religious identity, belief, and practice; and acknowledge the reality of nonexclusive/multiple religious beliefs, practices, and identities. Scholars must also take responsibility for developing a clear and nuanced definition of religion, abandon exceptionalist thinking, and seek to discover common patterns of religious change across societies. Conceptual and measurement tools at the disposal of social scientists of religion should enable us to perceive and understand the converging changes of religion in China, the United States, and other societies, without ignoring their historical differences and contemporary particularities.